How I treat FLT3-mutated AML - Pratz, Keith W. (Blood, 2017)
FLT3-mutated acute myeloid leukemia (AML), despite not being recognized as a distinct entity in the World Health Organization (WHO) classification system, is readily recognized as a particular challenge by clinical specialists who treat acute leukemia. This is especially true with regards to the patients harboring the most common type of FLT3 mutation, the internal tandem duplication (FLT3-ITD) mutation. Here we present 4 patient cases from our institution and discuss how our management reflects what we have learned about this subtype of the disease. We also reflect on how we anticipate the management might change in the near future, with the emergence of clinically useful tyrosine kinase inhibitors.